Single-Cell RNA Sequencing Reveals the Difference in Human Normal and Degenerative Nucleus Pulposus Tissue Profiles and Cellular Interactions - Li, Zhencong; Ye, Dongping; Dai, Libing; Xu, Yude; Wu, Hao; Luo, Wei; Liu, Yiming; Yao, Xiguan; Wang, Peigeng; Miao, Haixiong; Xu, Jiake; Liang, Weiguo (Frontiers in Cell and Developmental Biology, 2022)
Background: The nucleus pulposus is a constituent structure of the human intervertebral disc, and its degeneration can cause Intervertebral disc degeneration (IDD). Methods: Through bioinformatics analysis, the single-cell transcriptome sequencing expression profiles of human normal nucleus pulposus cells (NNP) and human degenerative nucleus pulposus cells (DNP) were compared to clarify the transcriptome differential expression profiles of human normal and human degenerative nucleus pulposus cells. Results: Nine cell types were identified, which were Chondrocyte1, Chondrocyte2, Chondrocyte3, Chondrocyte4, Chondrocyte5, Endothelial, Macrophage, Neutrophil, and T cells. Analysis of the proportion of chondrocytes in different tissues revealed that chondrocyte 1 accounted for a higher proportion of normal nucleus pulposus cells and highly expressed COL2A1 compared with degenerated nucleus pulposus cells; chondrocyte 2, chondrocyte 3, chondrocyte 4, and chondrocyte 5 accounted for a higher proportion of degenerated nucleus pulposus cells compared with normal nucleus pulposus cells. Among them, chondrocyte 2 was an inhibitory calcified chondrocyte with high expression of MGP, Chondrocytes 3 were fibrochondrocytes with high expression of COL1A1, Chondrocytes 4 are chondrocytes that highly express pain inflammatory genes such as PTGES, Chondrocytes 5 were calcified chondrocytes with high expression of FN1. Cell trajectory analysis revealed that chondrocyte 1 was at the beginning of the trajectory and chondrocyte 3 was at the end of the trajectory. Conclusion: After functional identification of the specifically expressed genes in five chondrocytes, it was found that chondrocyte 1 was a chondrocyte with high expression of COL2A1, COL9A2, COL11A2, and CHRDL2 in a high proportion of normal nucleus pulposus cells, and chondrocyte 3 was a fibrochondrocyte with high expression of COL1A1, COL6A3, COL1A2, COL3A1, AQP1, and COL15A1 in an increased proportion during nucleus pulposus cell degeneration. Through cell trajectory analysis, it was found that chondrocytes 5 specifically expressing FN1, SESN2, and GDF15 may be the key cells leading to degeneration of nucleus pulposus cells. Chondrocytes 2 expressing MGP, MT1G, and GPX3 may play a role in reversing calcification and degeneration, and chondrocytes 4 expressing PTGES, TREM1, and TIMP1 may play a role in disc degeneration pain and inflammation.